PERANAN ORANGTUA DALAM MEMBANGUN MANAJEMEN KEDISIPLINAN MELALUI ATURAN DAN BATASAN DI RUMAH UNTUK ANAK DI RA NURUL ULUM PONCOKUSUMO-MALANG - Ayu Putriana, Irma (JURALIANSI: Jurnal Lingkup Anak Usia Dini, 2025)
The role of parents in providing guidance is very influential in the growth and development of children. Children will see role models from both parents until the time the child will grow up. This is determined by the concept of parenting patterns given to children. The purpose of this study is to describe the role of parents in instilling a character of discipline and the supporting and inhibiting factors in the process of implementation at home for children in group B at RA Nurul Ulum Poncokusumo-Malang. The research methodology used is qualitative-descriptive, with data collection techniques of observation, interviews, and documentation. The results and discussions obtained have been triangulated to find the validity of the data, findings of the role of parents in instilling a character of discipline to design a balanced parenting pattern. The goal of discipline is a priority in child development, because it will support children's lives in understanding rules and boundaries everywhere. The character of discipline is very important and will be found in the social environment and the work environment. Therefore, education at home and at school provides a pattern of habits for children related to discipline patterns. Factors that influence if parents are unable to provide time for children to provide guidance during the growth period of early childhood. Furthermore, many parents are busy working without supervising their children at home or using technology. This hinders children from developing a disciplined character, a trait that will carry with them into adulthood. Furthermore, a child's disciplined character will stabilize their social and emotional development.